Experimental study on the performance of vortex tube cooling device on a cooling jacket - Lim, Sheh Hong; Muhammad Fadhli, Suhaimi; Mohd Hazwan, Yusof (IOP Publishing, 2020)
A vortex tube is an intriguing simple device which is capable of generating cold and hot streams from a single compressed fluid supply at room temperature. The vortex tube does not require any refrigerants or chemicals to operate which makes it an environmentally friendly device. Still, as a well cooling device, there are fewer or no research works that were conducted on the application of vortex tube. So, the application of vortex tube as a cooling device on a cooling jacket is less explored. Hence, the performance of this application on experimental research is unclear. Therefore, the objectives for this research are to determine the performance of vortex tube as a cooling device on a cooling jacket at different cold mass flow rate and also to determine the performance of vortex tube as a cooling device on a cooling jacket at different inlet pressure. The performance of vortex tube on the cooling jacket is experimented with different cold mass flow rate ranging from 30L/min to 90L/min and different inlet pressure ranging from 200kPa to 500kPa. Both parameters were with several condition, which are conducted at indoor condition, inside an air-ventilated room and outdoor condition, under the sunlight. At the end of the experiment, 90L/min and 500kPa were the optimum value for the performance of vortex tube. It can be concluded that the higher the inlet pressure supplied to the vortex tube, the lower the air temperature produced, and the higher the cold mass flow rate, enables lower cold air generated to the cooling jacket.